Polypharmacy, hospitalization, and mortality risk: a nationwide cohort study - Chang, Tae Ik; Park, Haeyong; Kim, Dong Wook; Jeon, Eun Kyung; Rhee, Connie M.; Kalantar-Zadeh, Kamyar; Kang, Ea Wha; Kang, Shin-Wook; Han, Seung Hyeok (Scientific reports, 2020)
Polypharmacy is a growing and major public health issue, particularly in the geriatric population. This study aimed to examine the association between polypharmacy and the risk of hospitalization and mortality. We included 3,007,620 elderly individuals aged ≥ 65 years who had at least one routinely-prescribed medication but had no prior hospitalization within a year. The primary exposures of interest were number of daily prescribed medications (1–2, 3–4, 5–6, 7–8, 9–10, and ≥ 11) and presence of polypharmacy (≥ 5 prescription drugs per day). The corresponding comparators were the lowest number of medications (1–2) and absence of polypharmacy. The study outcomes were hospitalization and all-cause death. The median age of participants was 72 years and 39.5% were men. Approximately, 46.6% of participants experienced polypharmacy. Over a median follow-up of 5.0 years, 2,028,062 (67.4%) hospitalizations and 459,076 (15.3%) all-cause deaths were observed. An incrementally higher number of daily prescribed medications was found to be associated with increasingly higher risk for hospitalization and mortality. These associations were consistent across subgroups of age, sex, residential area, and comorbidities. Furthermore, polypharmacy was associated with greater risk of hospitalization and death: adjusted HRs (95% CIs) were 1.18 (1.18–1.19) and 1.25 (1.24–1.25) in the overall and 1.16 (1.16–1.17) and 1.25 (1.24–1.25) in the matched cohorts, respectively. Hence, polypharmacy was associated with a higher risk of hospitalization and all-cause death among elderly individuals.